Coordination difficulties, IQ and psychopathology in children with high-risk copy number variants. Issue 2 (19th January 2021) - Cunningham, Adam C.; Hall, Jeremy; Owen, Michael J.; van den Bree, Marianne B. M.
Abstract: Background: The prevalence and impact of motor coordination difficulties in children with copy number variants associated with neurodevelopmental disorders (ND-CNVs) remains unknown. This study aims to advance understanding of motor coordination difficulties in children with ND-CNVs and establish relationships between intelligence quotient (IQ) and psychopathology. Methods: 169 children with an ND-CNV (67% male, median age = 8.88 years, range 6.02–14.81) and 72 closest-in-age unaffected siblings (controls; 55% male, median age = 10.41 years, s.d. = 3.04, range 5.89–14.75) were assessed with the Developmental Coordination Disorder Questionnaire, alongside psychiatric interviews and standardised assessments of IQ. Results: The children with ND-CNVs had poorer coordination ability ( b = 28.98, p < 0.001) and 91% of children with an ND-CNV screened positive for suspected developmental coordination disorder, compared to 19% of controls (OR = 42.53, p < 0.001). There was no difference in coordination ability between ND-CNV genotypes ( F = 1.47, p = 0.184). Poorer coordination in children with ND-CNV was associated with more attention deficit hyperactivity disorder (ADHD) ( β = −0.18, p = 0.021) and autism spectrum disorder trait ( β = −0.46, p < 0.001) symptoms, along with lower full-scale ( ß = 0.21, p = 0.011), performance ( β = −0.20, p = 0.015) and verbal IQ ( β = 0.17, p = 0.036). Mediation analysis indicated that coordination ability was a full mediator of anxiety symptoms (69% mediated, p = 0.012), and a partial mediator of ADHD (51%, p = 0.001) and autism spectrum disorder trait symptoms (66%, p < 0.001) as well as full scale IQ (40%, p = 0.002), performance IQ (40%, p = 0.005) and verbal IQ (38%, p = 0.006) scores. Conclusions: The findings indicate that poor motor coordination is highly prevalent and closely linked to risk of mental health disorder and lower intellectual function in children with ND-CNVs. Future research should explore whether early interventions for poor coordination ability could ameliorate neurodevelopmental risk.